PENDIDIK BERKARAKTER SUFI : Studi Analisis Tafsir Al-Qur’an Surat Al-Kahfi Ayat 17 - Siti Alfiatun Hasanah (Al-Dirayah, 2019)
In the view of Islam, educator essentially is the Prophet’s heir. He has a great responsibility to build the student’s character in order to be good and knowledgable. This is in accordance to the purpose of man’s creation, i.e. to worship Allah. Thus the main purpose of education is to direct mankind to in total obedience to Allah who are able to maintain the earth (khalifah fil ‘ardh) based on divine values. Educator therefore should become a figure who can the divine mission and spread it The divinemission of an educator should be realized in a sufistic character by educating his students both intellectually and spiritually.